REVEALING PROCESS-BASED AND WRITERS’ CHOICE OF ACADEMIC ESSAY WRITING IN UNDERGRADUATE EFL LEARNERS - Rahmawati Auliyah; Farouk Imam Arrasyid (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
This research are to describe the process-based academic writing plays the role in essay creationin the argumentative essay from EFL learners; to describe the writer’s choice contributing in academic essay writing of EFL in undergraduate by using rhetorical patterns; and to describe the weaknesses and strengths of process-based and writer’s choice role; This research uses the descriptive qualitative. The data sources of this research are argumentative essays from ELTD, sixth semester in undergraduate IAIN SNJ Cirebon. The text was taken from the students who followed GBL lesson in previous semester. The instrument is the researchers theirself. The techniques of collecting data that is used by the researchers are questionnaire, interview transcript, audio recording and document. The result of this research is different with the previous research. In this research, the researcherss shows essay’s writing process in detail, contribution of rhetorical patterns in essay’s creation and how strength and weakness the process also the pattern in essay. To the role of process-based stages here are more than half of efforts in making essay, means certain stages are very useful to the students as the author here. The examples are pre writing, editing and revising, and responding. Then, the patterns help the students as the author to arrange their essay. Both are giving big contribution to communicate the text to the readers. This is such as using marker (Mk 1, Mk 2 and Mk 3) as the signal or bridge among the sentence or the paragraph. However, both of them still have their own to be applied to the EFL learners